2020
DOI: 10.1088/1757-899x/998/1/012032
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Testing and Numerical Analysis of Flax/Glass Epoxy Hybrid Composite Material

Abstract: The natural fibres, as reinforcing medium will tremendously use in polymer composite industries due to rapid development of research in this field to maintain the sustainable materials towards its application. In this paper, Bidirectional woven E-Glass and Flax Fabrics with Epoxy resin were used to fabricate the two different composites with (0°, 45°) orientation by hand layup method. Laminate-1 made of four flax/epoxy layers and four Glass/Epoxy layers consecutively arranged one after the other, Laminate-2 ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Gupta [64] investigated the static behavior of F/G biocomposites and reported that the lay-up sequence GFGH was better than the FGFH arrangement in terms of tensile, flexural, compressive, and impact properties. Kumar et al [65] determined the properties of 8-layered F/G epoxy composites. Ramesh [13] conducted the SEM analysis of F/G epoxy composites and reported that the specimens with 0 • fiber orientation outperformed that of 90 • fiber orientation.…”
Section: Flax Fibermentioning
confidence: 99%
“…Gupta [64] investigated the static behavior of F/G biocomposites and reported that the lay-up sequence GFGH was better than the FGFH arrangement in terms of tensile, flexural, compressive, and impact properties. Kumar et al [65] determined the properties of 8-layered F/G epoxy composites. Ramesh [13] conducted the SEM analysis of F/G epoxy composites and reported that the specimens with 0 • fiber orientation outperformed that of 90 • fiber orientation.…”
Section: Flax Fibermentioning
confidence: 99%